2015
DOI: 10.4187/respcare.04132
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mean Platelet Volume in Chronic Obstructive Pulmonary Disease Exacerbation

Abstract: BACKGROUND: Studies have supported the correlation between mean platelet volume and COPD. However, there are limited data on the relationship between COPD exacerbation and mean platelet volume. We aimed to evaluate the mean platelet volume trend in patients with COPD exacerbation. METHODS: A total of 81 subjects, 62 men and 19 women, who were admitted to the hospital because of exacerbation of COPD during 9 months, were enrolled in this prospective observational study. The levels of mean platelet volume, C-rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
2
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 25 publications
4
27
2
1
Order By: Relevance
“…In contrast to our study, several other studies showed that AECOPD were more commonly seen in males. 1,2,[11][12][13][14] The gender difference was not significant in our study.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…In contrast to our study, several other studies showed that AECOPD were more commonly seen in males. 1,2,[11][12][13][14] The gender difference was not significant in our study.…”
Section: Discussionmentioning
confidence: 71%
“…1 Chronic obstructive pulmonary disease is a major global health problem with an upward trend. 2 It is characterised by progressive air flow limitation that is not fully reversible and is associated with an abnormal inflammatory response of the lung to noxious particles or gases. 2,3 In some patients there are episodes of increased symptoms called as acute exacerbations.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations